Brainstem and Hypothalamic Regulation of Sleep Pressure and Rebound in Newborn Rats. - Todd, William D.; Gibson, James L.; Shaw, Cynthia S. (Behavioral Neuroscience, 2010)
Sleep pressure and rebound comprise the two compensatory or “homeostatic” responses to sleep deprivation. Although sleep pressure is expressed by infant rats as early as postnatal day (P)5. sleep rebound does not appear to emerge until after PI 1. We reexamined the developmental expression of these sleep-regulatory processes in P2 and P8 rats by depriving them of sleep for 30 min using a cold, arousing stimulus delivered to a cold-sensitive region of the snout. This method effectively increased sleep pressure over the 30-min period (i.e., increases in the number of arousing stimuli presented over time). Moreover, sleep rebound (i.e., increased sleep during the recovery period) is demonstrated for the first time at these ages. Next, we showed that precollicular transections in P2 rats prevent sleep rebound without affecting sleep pressure, suggesting that the brainstem is sufficient to support sleep pressure, but sleep rebound depends on neural mechanisms that lie rostral to the transection. Finally, again in P2 rats. we used c-fos immunohistochemistry to examine neural activation throughout the neuraxis during sleep deprivation and recovery. Sleep deprivation and rebound were accompanied by significant increases in neural activation in both brainstem and hypothalamic nuclei, including the ventrolateral preoptic area and median preoptic nucleus. This early developmental expression of sleep pressure and rebound and the apparent involvement of brainstem and hypothalamic structures in their expression further solidify the notion that sleep-wake processes in newborns — defined at these ages without reference to state-dependent EEG activity — provide the foundation on which the more familiar processes of adults are built. Reprinted by permission of the publisher.